CART Immunotherapy: Development, Success, and Translation to Malignant Gliomas and Other Solid Tumors - Filley, Anna C.; Henriquez, Mario; Dey, Mahua (Frontiers in Oncology, 2018)
T cell chimeric antigen receptor (CAR) technology has allowed for the introduction of a high degree of tumor selectivity into adoptive cell transfer therapies. Evolution of this technology has produced a robust antitumor immunotherapeutic strategy that has resulted in dramatic outcomes in liquid cancers. CAR-expressing T-cells (CARTs) targeting CD19 and CD20 have been successfully used in the treatment of hematologic malignancies, producing sustained tumor regressions in a majority of treated patients. These encouraging results have led to a historic and unprecedented FDA approval of CTL019, Novartis’ CAR T-cell therapy for the treatment of children and young adults with relapsed or refractory B-cell acute lymphoblastic leukemia (ALL). However, the translation of this technology to solid tumors, like malignant gliomas (MG), has thus far been unsuccessful. This review provides a timely analysis of the factors leading to the success of CART immunotherapy in the setting of hematologic malignancies, barriers limiting its success in the treatment of solid tumors, and approaches to overcome these challenges and allow the application of CART immunotherapy as a treatment modality for refractory tumors, like malignant gliomas, that are in desperate need of effective therapies.